2019
DOI: 10.1055/a-0838-6371
|View full text |Cite
|
Sign up to set email alerts
|

Perceived distress, personality characteristics, coping strategies and psychosocial impairments in a national German multicenter cohort of patients with Crohn’s disease and ulcerative colitis

Abstract: Background and aims This study examined differences in personality, psychological distress, and stress coping in inflammatory bowel disease (IBD) depending on type of disease and disease activity. We compared patients suffering from Crohn’s disease (CD) and ulcerative colitis (UC) with controls. While the literature is replete with distinctive features of the pathogenesis of IBD, the specific differences in psychological impairments are not well studied. Methods In this German national multicenter st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Specifically, an avoidant attachment style in UC is a moderator between negative childhood experiences and disease activity, while this association could not be shown in CD ( Caplan et al, 2014 ). UC patients seem to have more attachment-related anxiety than HC and therefore experience more perceived stress, while another study found especially CD to be associated with higher levels of emotional distress than UC or HC ( Agostini et al, 2016 ; Petruo et al, 2019 ). Deficits in mentalization and attachment insecurity may lead, via a decreased medical adherence and a decreased social support, to a worsening of the IBD course and afterward to more IBD-related stress and further deficits in a vicious circle ( Colonnello and Agostini, 2020 ).…”
Section: Introductionmentioning
confidence: 95%
“…Specifically, an avoidant attachment style in UC is a moderator between negative childhood experiences and disease activity, while this association could not be shown in CD ( Caplan et al, 2014 ). UC patients seem to have more attachment-related anxiety than HC and therefore experience more perceived stress, while another study found especially CD to be associated with higher levels of emotional distress than UC or HC ( Agostini et al, 2016 ; Petruo et al, 2019 ). Deficits in mentalization and attachment insecurity may lead, via a decreased medical adherence and a decreased social support, to a worsening of the IBD course and afterward to more IBD-related stress and further deficits in a vicious circle ( Colonnello and Agostini, 2020 ).…”
Section: Introductionmentioning
confidence: 95%
“…Some medical therapies are effective in both diseases; other therapies work well in one, but not the other 21 . There is also evidence of different prevalence of affective symptoms and different strategies of coping with psychosocial stress 22,23 . In this regard, a study using near infrared spectroscopy (NIRS) provided preliminary evidence for neural differences between CD and UC in terms of a decreased activity in the frontal lobe of UC patients compared to CD, 24 but topologically more distinct evidence, such as high‐resolution MRI data, is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The adaptive immune system is considered the key regulator of the pathogenesis of CD [ 3 ]. When the intestinal barrier is broken, pattern recognition receptors, such as TLR [ 52 ] and NLR [ 53 ], recognize the microbe-associated molecular patterns, thus promoting the activation and differentiation of T cells [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis is complex, the decades of studies have illustrated that CD is caused by environmental factors that broke the mucosal barrier and increased the luminal antigens into the lamina propria [ 2 ]. Different innate immune cells, like dendritic cells, recognize the antigens via pattern recognition receptors, such as Toll-like receptors (TLR) and NLR, and then regulate the activation of T cells [ 3 ].…”
Section: Introductionmentioning
confidence: 99%